A Case Study on Students’ Difficulties in Learning English at Vocational High School - Ocktavia, Lulu; Srisudarso, Mansyur; Mobit, Mobit (FKIP - Universitas Riau, 2025)
The aimed of this research was to find out students' difficulties in Learning English and the teachers' efforts to solve students' difficulties in Learning English at Vocational High School. The research used a qualitative approach with case study method. The subject of this research were six students of the Accounting and Finance Department in the twelfth class one of the vocational high schools in Karawang. The research used observation and interviews to collect the data. The result of the research showed that the ability to speak and listen is the most difficult to acquire by the students due to lack of confidence, limited vocabulary, and people’s perception when they speak in a wrong spelling. The solution suggested by the teacher involves quizzes with a gamification approach and do more to implement the used of English in school. Therefore, students in Vocational High Schools can further develop their abilities in English learning.